Twobandad Japanese Weevil, Pseudocneorhinus bifasciatus Roelofs (Insecta: Coleoptera: Curculionidae) - Jamba Gyeltshen; Amanda Hodges (EDIS, 2006)
The twobanded Japanese weevil, Pseudocneorhinus bifasciatus (Roelofs), first collected in the United States in 1914 near Philadelphia, was most likely introduced with infested nursery stock from Japan (Wheeler and Boyd 2005). With a host range of over 100 plant species, the twobanded Japanese weevil is recognized in the northeastern and midwestern United States as an important pest of landscape plantings (Wheeler and Boyd 2005). Although not a pest of major concern yet in the southeastern states, it is likely to extend its range due to movement of nursery stock. In July 2005, two specimens of the twobanded Japanese weevil were collected at Chipley, Florida, which is in Washington county (Thomas 2005). This document is EENY-361 (IN646), one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Original publication date December 2005.